Spiritual Discernment, the Incorporated Organization, and Corporate Law: The Case of Quaker Business Method - Burton, Nicholas (Religions, 2019)
The purpose of this paper is to examine the extent to which practices from the spiritual traditionsin our case, spiritual discernmentmay offer opportunities for management innovation in non-religious organizations in designing collaborative and participative decision-making processes. We examine the case of a spiritual discernment practice associated with the Religious Society of Friends (Quakers) in the UKknown as the Quaker Business Method (QBM)to help illuminate the opportunities of spiritual discernment in private limited companies. Given that the majority of non-religious, trading organizations are structured as private limited companies, our paper addresses the extent to which QBM can be utilized by such entities. Thus, we bring religion and corporate law into conversation to address this under-explored terrain. We find that embedding many elements of Quaker spiritual discernment in private limited companies pose non-trivial challenges. However, many of these challenges can be overcome so long as those involved in managing and owning organizations actively engage with corporate law, and specifically consider the benefits of adopting bespoke articles of association or entering into a separate shareholder agreement to reflect the practice of spiritual discernment. We necessarily adopt a practice-orientated perspective, and conclude by proposing new pathways for future research.